The Relationship between Arabic Language Proficiency and Level of Politeness in Indonesian Islamic Boarding Schools - Surya Hidayat; Aulia Rahman; Alvian Izzul Fikri; Azizah; Syaiful Mustofa; M Yusuf Abdullah; Fadlan Masykura Setiadi (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2024)
This study investigates the potential relationship between Arabic language proficiency and politeness level. Arabic has an important role in transforming the values of ethics and morality because learning Arabic does not only cover aspects of grammar and vocabulary, but also involves understanding culture and social norms. The aim of this research is to examine the correlation between proficiency in language mastery and politeness levels. This study employs a quantitative approach through a correlational method. The collection of data involves the utilization of learning evaluation documents and politeness scales. Data analysis is conducted through simple linear regression, facilitated by the Statistical Package for the Social Sciences (SPSS) for calculation purposes. Hypothesis testing using simple linear regression test is used to measure the influence of one independent variable on the dependent variable. The results showed that there was no relationship between ability and politeness as seen from the significance value of 0.319> 0.05. This can also be proven by the magnitude of the coefficient of determination or the amount of influence given by variable X to variable Y. It is hoped that this research can be a reference for similar research in the future.